Implementation and Regulation of Sharia Digital Financial Systems in Indonesia - Pramono, Alya Fatimah; Muthoifin, Muthoifin (Universitas Muhammadiyah Surakarta, 2025)
Objective: To reveal gaps in understanding the application of fatwas in Islamic fintech, obstacles such as low literacy and weak supervision, and proposals for digital adaptation innovations. Theoretical Framework: Based on sharia principles (prohibition of usury, gharar, maysir) with the evolution of the concept of electronic money from the Islamic empire era to modern regulations such as Law No. 21/2008 and POJK No. 28/2019. Literature Review: A review of previous studies reveals gaps such as a lack of analysis of the implementation of DSN-MUI fatwas (No. 116/2017, 117/2018), protection of sharia e-wallet data, the role of OJK, and DSN-MUI supervision, as well as the potential of sharia fintech despite low literacy. Methods: A normative legal qualitative approach with secondary data from literature, journals, PBI No. 23/6/2021, DSN-MUI fatwa, literature review, evolutionary synthesis, and case studies of Islamic fintech banking. Results: Sharia banking assets grew to IDR 980.30 trillion (2024, +10%), but market share remained at 7 8%; opportunities for BSI and LinkAja Syariah to reach the unbanked 50%, challenges of real-time DPS supervision and BASYARNAS MUI arbitration compared to non-sharia (OVO, GoPay). Implications: Strengthen regulations (mandatory arbitration clauses, AI DPS), literacy education via the BSI LinkAja platform (increase inclusion by 20%), global harmonization of AAOIFI for competitiveness and sustainability of the Islamic economy. Novelty: The first normative digital integrative approach synthesizing the evolution of sharia electronic money up to POJK 28/2019, a process-oriented compliance model proposed by the BASYARNAS-MUI cross-sector case study and the QRIS/PayLater halal filter, has not yet been comprehensively analyzed.